2019
DOI: 10.3897/rrpharmacology.5.34072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of physicians’ and senior medical students’ basic knowledge in treatment of chronic obstructive pulmonary disease

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is one of the most common pathologies of the respiratory system. This disease ranks third in the group of the main causes of death in the world. The effective treatment of COPD has been developed by today. However, a significant part of physicians has an insufficient amount of education in this matter. Materials and methods: The article represents the results of anonymous prospective survey within the ASCO project (full title – “Assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that causes persistent respiratory symptoms and airflow restriction, owing to airway and/or alveolar abnormalities ( 1 ). The World Health Organization survey in 2019 reported 380 million COPD cases in the world and more than 3 million patients annually die from this pathology, which is very alarming ( 2 , 3 ). The pathogenesis of COPD involves inflammation orchestrated by various inflammatory cells and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that causes persistent respiratory symptoms and airflow restriction, owing to airway and/or alveolar abnormalities ( 1 ). The World Health Organization survey in 2019 reported 380 million COPD cases in the world and more than 3 million patients annually die from this pathology, which is very alarming ( 2 , 3 ). The pathogenesis of COPD involves inflammation orchestrated by various inflammatory cells and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…Macrolides should be preferred if it is impossible to use aminopenicillins (idiosyncrasy, allergy), and also with a suspected "atypical" etiology of the disease (S. pneumoniae and M. рneumoniae) (Breitling et al 2018;Lee et al 2018). It is worth noting that parenteral forms of drugs during out-patient treatment do not have proven advantages over oral ones, at the same time, they pose a threat to the development of post-injection complications in the form of abscesses and require additional costs for administration (Chuchalin et al 2010;Bontsevich et al 2019a). Only 9.1% of the senior students answered this question correctly, 27.2% of the students answered partially correctly, and 63.7% gave the wrong answer.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D has been shown to reduce the level of oxidative stress and the number of circulating interleukins (e.g., 6,9,13), which means that vitamin D treatment of COPD patients can improve their symptoms [101]. Khan et al revealed a relationship between serum vitamin D levels and COPD progression [109].…”
Section: Discussionmentioning
confidence: 99%
“…Acute exacerbations and comorbidities are important prognostic factors for the severity of COPD [ 2 , 4 ]. COPD is an underdiagnosed disease with increasing morbidity and mortality worldwide [ 4 , 5 ], and is projected by the World Health Organization (WHO) to become the third leading cause of death by 2022 [ 6 ]. Its causes include changing smoking habits, an ageing population, and certain respiratory infections [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation